1996
DOI: 10.1007/bf02305790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of colorectal cancer: Metastases in lymph nodes <5 mm in size

Abstract: Most metastatic lymph nodes were < 5 mm in diameter. Based on our results, the size of lymph node metastases do not affect disease-free or overall survival in colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 10 publications
3
59
0
3
Order By: Relevance
“…33 The size of lymph nodes, however, has received attention in only a few studies. [20][21][22][23] Using advanced lymph node dissection techniques, we collected a relatively large number of colon cancer cases with optimal lymph node staging starting in 2007. 14 As the study was conducted at a single center and a standardized dissection technique was used, we were able to reduce confounding factors that might hamper large database studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The size of lymph nodes, however, has received attention in only a few studies. [20][21][22][23] Using advanced lymph node dissection techniques, we collected a relatively large number of colon cancer cases with optimal lymph node staging starting in 2007. 14 As the study was conducted at a single center and a standardized dissection technique was used, we were able to reduce confounding factors that might hamper large database studies.…”
Section: Discussionmentioning
confidence: 99%
“…18 Our impression, however, is that larger lymph nodes are often not involved in metastatic disease but show lymphofollicular hyperplasia. [19][20][21][22][23] This might explain the relatively disappointing results of diagnosis based on radiological lymph node status assignment, which is mainly dependent upon lymph node size. 24 Moreover, one could hypothesize that lymphatic hyperplasia in colon cancer could be a prognostic marker indicating an especially effective immunological response against the cancer.…”
mentioning
confidence: 99%
“…The small size of involved lymph nodes in some cases is relevant. It has been reported that up to 70% of lymph nodes with metastases are <5 mm in diameter [23]. Such lymph nodes can easily be missed if palpation is the main technique used by the pathologist to identify lymph nodes.…”
Section: The Role Of the Surgery/pathology Team In Lymph Node Retrievalmentioning
confidence: 99%
“…Conventional methods for examining lymph nodes have specific limitations and are subject to sampling error, which increases the risk of understaging. Since up to 70% of tumor-involved lymph nodes are less than 0.5 cm in diameter, nodes that contain small metastases can be easily missed in the gross dissection or microscopic examination (5,6).…”
Section: Introductionmentioning
confidence: 99%